Thursday
December 12, 2013

# Posts by Margie

Total # Posts: 200

Another problem to check..please check my work...
(-2x^2y)^3*(5xy^3)^2=(-2x^2y)^3 = -8 x^6 y^3 *Is this correct.? (-2x^2y)^3 * (5xy^3)^2 = (-8x^6y^3) * (25x^2y^6) = -200x^8y^9 When you have the same base, you add exponents when multiplying. For example, x^2 * x^3 = x^5. When you have the same base, you multiply exponents when...

(2x-3)(x^2+5x-3)=2x+10x^2-15x+9 *Is this correct.? this is a different problem... Here's how this one works out: ......x^2 + 5x - 3 ............2x - 3 ================== ...... -3x^2 - 15x + 9 2x^3 + 10x^2 - 6x ====================== 2x^3 + 7x^2 - 21x + 9 I hope this will ...

3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this correct.?- Remember to add exponents when multiplying with the same base. (3a^3b^2)(-a^3b - a^2b^2) = -3a^6b^3 - 3a^5b^4 I hope this will help.

math2(count iblis)
-y^3(2x^2y-4xy^2)=-2x^2y^4+4xy^6 *is this correct.? No, in the last term, the y should be to the fifth power (3+2)

math
sqrt3x^5y^14 To simplify: sqrt(3 x^5 y^14) The square root of x^4 is x^2. The square root of y^14 is y^7. Can you determine what to do now with those hints? I hope this will help.

math
-4x^2(3x^2-x+1)=-12x^4+4x^3-1x^2 *Is this correct.? The last term should be -4x^2

math
-4x^2(3x^2-x+1) Multiply it term by term, and I will, or someone will check you.